Study Of Nutrient Foramina In Adult Human Femur Bones - Gupta, Anil Kumar; Ambekar, M. N. (Journal of Nepalgunj Medical College, 2018)
Background: The role of nutrient foramen (NF) in nutrition and growth of the bones is evident from term Nutrient itself. The nutrient foramen is opening of nutrient canal on the surface of shaft of the bone which conducts the nutrient artery and the peripheral nerves to bones. Long bones receive most of the interosseous blood supply (70% to 80%) from the nutrient arteries and remaning (20% to 30%) through the periosteal vessels. Nutrient arteries play an important role in nutrition and growth of the bones particularly during early phases of ossification and growth. The present study is of great importance to orthopedic surgeons in planning repair of fracture, amputation and bone grafting procedures.Aim and objective of study: A study regarding nutrient foramina in femur was not conducted in the past in Nepal. Its importance in orthopedic procedures has inspired us to undertake this study.Materials and methods: This study was conducted on 100 adult dry femur bones (50 right and 50 left). All the important parameters were studied using osteometric board, vernier calipers, and needles of different gauges.Results: Mean distance of nutrient foramen from upper end was 18.09 cms. The most common location of NF was on lateral surface 58.8%. In 71% femur only one NF was seen, while 25% had two NF, 1% femur had three NF and 3% femur had no NFs. In 64.5% femur big size or dominant NFs were seen in present study.Conclusions: The findings of this study on nutrient foramen adds to the information from studies in the past by other authors. The fact that maximum number of the nutrient foramina are present in the middle third of the shaft of the femur is of clinical importance for proper diagnosis, planning of surgery and predict the prognosis. JNGMC,  Vol. 14 No. 2 December 2016, Page: 44-49